Prospective analysis of craniofacial soccer incidents during FIFA competitions: an observational study - Mateus de Azevedo KINALSKI; Kaue COLLARES; Marcos Britto CORREA (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract The aim of this prospective epidemiological study was to evaluate the occurrence of incidents involving the craniofacial region of soccer players during three official FIFA competitions. The craniofacial incidents were identified by video analysis of all 144 matches of two FIFA World Cups (2014/2018) and the 2017 FIFA Confederations Cup. Data collection included incident type, incident severity, site affected, incident cause and referee decision. The multivariate Poisson regression model was performed to analyze the associations between covariates. A total of 238 incidents were observed in the craniofacial region (1.6 incidents/match), representing a rate of 48.5 incidents per 1000 hours. At least 80.6% of the matches presented at least one incident, and, in more than 60%, the referee's decision was no foul. According to severity, 26.8% of the incidents were classified as having mild or high severity. Incidents involving lacerations or fracture presented higher severity compared with hits (IRR 3.45[95%CI: 1.89-6.30]). Head-to-head impacts showed an incidence of severe incidents twice as high as those involving upper extremities (IRR 2.01[95%CI:1.07-3.76]). A high number of craniofacial incidents were observed in the last FIFA competitions. Head-to-head impacts and lacerations or fractures were associated with higher incident severity.